2010
DOI: 10.1021/cg1004352
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Detection of Organophosphate Pesticide Based on a Metal−Organic Framework Derived from Biphenyltetracarboxylic Acid

Abstract: A new conjugated metal-organic framework based on 2,2 0 ,4,4 0 -biphenyltetracarboxylic acid with a uninodal fiveconnected hexagonal boron nitride net (bnn) was synthesized, which represented the first example of metal-organic frameworks capable of adsorbing a trace level of organophosphate pestcide for efficient detection via stripping voltammetric analysis. A detection limit of 0.006 μg 3 mL -1 was obtained with the calculation based on a signal-noise ratio equal to 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…MOFs are usually prepared under hydrothermal, solvothermal, and ionothermal approaches [14][15][16][17]. However, considering the energies and environments required, it is extremely difficult to use the abovementioned approaches for the large-scale preparation of MOFs for industrial processes.…”
Section: Introductionmentioning
confidence: 99%
“…MOFs are usually prepared under hydrothermal, solvothermal, and ionothermal approaches [14][15][16][17]. However, considering the energies and environments required, it is extremely difficult to use the abovementioned approaches for the large-scale preparation of MOFs for industrial processes.…”
Section: Introductionmentioning
confidence: 99%
“…A strong peak appeared at 586 cm −1 , corresponding to the vibration modes of all spinel compounds, which is attributed to the M-O stretching bands in tetrahedral complexes. [43][44][45][46] The absorption broad band at 3433 cm −1 represents the stretching mode of H 2 O molecules and OH groups. The band around 1627 cm −1 corresponds to the bending mode of H 2 O molecules [47] (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…While the recovery of doped pesticides was very high (78-107%), identification and quantification of the pesticides was done using GC-MS, which added significant time and cost to the process. In the same year, researchers reported that a biphenyl-containing MOF could bind low concentrations of organophosphate pesticides, with the success of such binding measured using electrochemical analysis (Wen et al, 2010). A variety of other electrochemical-based detections of pesticide binding in MOFs have since been reported (Nagabooshanam et al, 2019;Tu et al, 2019;Chansi et al, 2020).…”
Section: Metal-organic Framework Pesticide Detectionmentioning
confidence: 99%